Probing the nanomechanics of interfacial interactions between hydrophobic surfaces - Lu, Liqun; Wang, Fengjuan; Wang, Yuncheng; Zhang, Jiawen; Xiang, Li; Liu, Zhiyong; Jiang, Jinyang (Frontiers in Physics, 2024)
Hydrophobic interactions are widely applied in diverse fields, yet the effect of hydrophobicity degree on the interactions between hydrophobic surfaces are still unaddressed, limiting the development of functional hydrophobic surface. In this study, the interfacial interactions and configuration of hydrophobic chains on surfaces with ranging hydrophobicity are surveyed by surface forces apparatus. It is unraveled that with partial hydrophobicity, long-range electrical double layer repulsive force pertains between surfaces; while between fully hydrophobized surfaces, only steric hindrance is observed, and the hydrophobic chains maintain configuration even after long time compression. Our findings provide useful implications in understanding hydrophobic interactions.